Effect of guard cells electroporation on drying kinetics and aroma compounds of Genovese basil (Ocimum basilicum L.) leaves. (December 2016) - Kwao, Stephen; Al-Hamimi, Said; Damas, María Elena Vicente; Rasmusson, Allan G.; Gómez Galindo, Federico
Abstract: In this study the effect of the application of pulsed electric fields as pre-treatment before air drying of basil leaves at 50 °C was investigated. The parameters of the electric treatment were designed in such a way that they either (i) electroporated the tissue reversibly (tissue remains viable) and without electroporating the guard cells in the stomata complex (65 pulses of 600 V/cm, 120 μs pulse width, 500 μs between pulses), (ii) electroporated the tissue reversibly causing the guard cells to irreversibly open the stomata (65 pulses of 600 V/cm, 150 μs pulse width, 760 μs between pulses), or (iii) irreversibly electroporated the tissue leading to cell death (65 pulses of 1500 V/cm, 150 μs pulse width, 760 μs between pulses). Results demonstrate that dehydration of basil leaves at 50 °C can be aided by the application of pulsed electric fields (PEF). If the applied PEF conditions are such that stomata are irreversibly opened while the rest of the tissue remains viable, the drying process is faster and the product keeps a better colour, is richer in aroma compounds and has better rehydration capacity than the untreated control. Irreversible tissue damage provoked by high intensity PEF drastically decreased the drying time but the measured quality characteristics of the dried leaves were inferior compared to those of the dried product when the stomatal function of the fresh leaf was selectively targeted. Industrial relevance: This paper addresses the ever-increasing global demand from consumers for high-quality foods, reporting a novel methodology which improves the quality of dried aromatic herbs using pulsed electric fields. Highlights: Reversible pulsed electric field is used as pre-treatment to dry basil. In the electroporated leaves, guard cells irreversibly open the stomata. Opened stomata during drying shortens drying times. Treated leaves keep better quality than the untreated control.